2009
DOI: 10.1177/186810260903800403
|View full text |Cite
|
Sign up to set email alerts
|

“Building a New Socialist Countryside” – Only a Political Slogan?

Abstract: In March 2006, China's National People's Congress officially promulgated the central government's intention to “build a new socialist countryside”, a new policy initiative and approach to rural development. Drawing on fieldwork conducted in two Chinese counties in 2008 and 2009, this article investigates how the new policy is being substantiated and implemented at the local level. It argues that by combining China's new fiscal system of transfer payments to poor local governments with administrative reforms, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 10 publications
1
53
0
Order By: Relevance
“…The findings of this study are consistent with other studies in rural China that have demonstrated that county officials dominate the implementation process of rural development initiatives, that they have clear ideas about which villages to select, and that focal or model villages (the main destination for higher-level government inspection teams) receive the largest portion of NCS funds passed down to the county (Ahlers and Schubert, 2009;Schubert and Ahlers, 2012). This reflects a broader notion in China that model villages will lead rural development, also described as "showcasing" (Smith, 2009;Ahlers and Schubert, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of this study are consistent with other studies in rural China that have demonstrated that county officials dominate the implementation process of rural development initiatives, that they have clear ideas about which villages to select, and that focal or model villages (the main destination for higher-level government inspection teams) receive the largest portion of NCS funds passed down to the county (Ahlers and Schubert, 2009;Schubert and Ahlers, 2012). This reflects a broader notion in China that model villages will lead rural development, also described as "showcasing" (Smith, 2009;Ahlers and Schubert, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…They encompass two broad priorities: improving living conditions (including poverty alleviation) and advanced production (supporting agricultural modernisation and specialisation). NSC-related funding is channelled through the fiscal transfer system and is available to all counties, not just poverty counties (Ahlers and Schubert, 2009).…”
Section: Results: Resource Allocation In Ji Countymentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of China's so-called "socialist market economy" is taking place within an authoritarian order which seems to be unchallenged by the great majority of the Chinese people. 1 Why is this so? Does modernization theory not apply to China?…”
Section: Introductionmentioning
confidence: 94%
“…34 33 Interview with the head of the Reform and Development Bureau, September 13, 2009. 32 For a detailed description of local XNCJS policy formulation, implementation and, in particular, XNCJS project application procedure and funding, see for example, Ahlers and Schubert [1]; Li [43]; Su [77]. 34 As the director of Qingyuan's Reform and Development Bureau (fagaiju) explained, investments in the development of the countryside (zhinong) have increased to almost 90% of the county budget in 2009 (Interview on September 13, 2009).…”
Section: Policy Implementationmentioning
confidence: 99%